Eating animals [videorecording (DVD)] - Portman, Natalie, 1981-; Foer, Jonathan Safran, 1977- (IFC Films, 2019)
Based on the bestselling book by Jonathan Safran Foer and narrated by co-producer Natalie Portman, this is an urgent, eye-opening look at the environmental, economic, and public health consequences of factory farming. It offers attainable, common-sense solutions to a growing crisis while making the case that ethical farming is not only an animal rights issue but also one that affects every aspect of life.